Best practices of Islamic leadership principles among principals of excellent secondary schools Malaysia - Salleh, Mohamad Johdi; Mohamad, Nazifah Alwani; Khalid, Robita (UNISZA, 2018)
The purpose of the study was to examine the best practice of Islamic leadership principles among principals of excellent secondary schools in Selangor, Malaysia. The lists of sixty principals as respondents and schools were obtained from the State Education Department of Selangor according to their GPS (Grade Point Standard) excellent achievement in the Lower Secondary Assessment in three consecutive years (2015, 2016, 2017). The study mainly referred to the principles of Islamic management (Khaliq, 2007), Islamic principles of educational leadership (Al-Hasani, 2009), dimensions of Transformational Leadership (Leithwood & Jantzi, 2000; Mohamad Johdi and Parvina, 2013), functions of Instructional Leadership (Hallinger & Murphy, 1987; Mohamad Johdi, 2014), fundamentals of Strategic Leadership (Davies & Davies, 2010; Hairuddin, 2016), and, characteristics of Islamic Exemplary Leadership (Kouzes and Posner, 2003; Mohamad Johdi and Robita, 2018). The self-administered questionnaire was then developed, modified, and validated as a mean of data collection and the findings were analyzed by using the Social Packages of Social Science version 23.0. It was very interesting to observe that all five principles of Islamic Educational Leadership were practiced at ‘Very High’ level by the respondents. More specifically, the result of the study showed that the highest score was ‘Self-Confidence’ with mean 4.870. The second highest was ‘Responsibility’ with mean score 4.830. The third and fourth were ‘Accountability’ with mean score 4.820, and, ‘Trust’ with mean score 4.800, respectively. Whilst, the lowest score was ‘Inspired a Shared-vision’ with mean score 4.470. Indeed, the study observed some indication for educational leaders, education officers and trainers to really consider the inclusion of these five Islamic leadership principles in the development of excellent educational leaders towards realization of Vision 2020 and Malaysian Education Blueprint 2013-2025 in the realm of IR 4.0.